2020
DOI: 10.1136/bmjophth-2019-000382
|View full text |Cite
|
Sign up to set email alerts
|

Retinal arteriolar oxygen saturation predicts the need for intravitreal aflibercept in patients with diabetic macular oedema

Abstract: ObjectiveGiven the increasing burden of repetitive intravitreal injections in diabetic macular oedema (DMO) treatment, non-invasive markers of treatment outcome are needed. Hence, we aimed to examine retinal oximetry parameters as markers of need for intravitreal aflibercept in patients with DMO.MethodsThis study was based on data from a 12-month clinical trial including 35 eyes of 25 patients with centre involving DMO. Retinal oximetry, visual acuity (VA) and central retinal thickness (CRT) were performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Retinal therapies considered in the studies found included panretinal photocoagulation, 180 anti-VEGF, 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 pars plana vitrectomy, 214 and steroids 215 , 216 , 217 for DME 181 , 182 , 183 , 185 , 187 , 188 , 191 , 192 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 210 , 212 , 213 , 214 <...…”
Section: Resultsmentioning
confidence: 99%
“…Retinal therapies considered in the studies found included panretinal photocoagulation, 180 anti-VEGF, 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 pars plana vitrectomy, 214 and steroids 215 , 216 , 217 for DME 181 , 182 , 183 , 185 , 187 , 188 , 191 , 192 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 210 , 212 , 213 , 214 <...…”
Section: Resultsmentioning
confidence: 99%
“…Retinal oximetry is a metabolic marker associated with retinal ischemia, which is a key factor in BRVO [4]. While it has been identified as a predictor of disease activity in diabetic macular edema [5], conflicting preliminary results have been presented in BRVO [6,7], with relevant clinical outcomes not sufficiently examined.…”
Section: Introductionmentioning
confidence: 99%